Monthly Variations of Physico-Chemical Factors of Keenjhar Lake, Sindh, Pakistan: Monthly Variations of Physico-Chemical Factors of Keenjhar Lake, Sindh, Pakistan - Rao, Shahina; Azmi, Muhammad Arshad; Rahman, Solaha (International Journal of Economic and Environmental Geology, 2019)
The present study was carried out with the aim to assess water quality using physico-chemical factors of Keenjhar lake. For this purpose, lake water was analyzed with regular intervals. The air temperature ranged between 21 °C to 38 °C, water temperature between 19 °C to 36 °C , pH 5.5 to 8, dissolved oxygen 2.26 mg/L to 6.81 mg/L, salinity 0.16 mg/L to 1.13 mg/L, alkalinity from 30 mg/L to 165 mg/L, acidity 8 to 110 mg/L, sulphate 2.6 mg/L to 310 mg/L, phosphate from 1 mg/L to 31 mg/L and nitrates 16 mg/L to 180 mg/L during 2006, 2007 and 2008. It was concluded that various parameters lie within the permissible range except in a few months and suitable for drinking, irrigation and fish culture purposes.